Knockout of angiotensin converting enzyme-2 receptor leads to morphological aberrations in rodent olfactory centers and dysfunctions associated with sense of smell - Mahajan, Sarang; Sen, Deepshikha; Sunil, Anantu; Srikanth, Priyadharshini; Marathe, Shruti D.; Shaw, Karishma; Sahare, Mahesh; Galande, Sanjeev; Abraham, Nixon M. (Frontiers in Neuroscience, 2023)
Neuronal morphological characterization and behavioral phenotyping in mouse models help dissecting neural mechanisms of brain disorders. Olfactory dysfunctions and other cognitive problems were widely reported in asymptomatic carriers and symptomatic patients infected with Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). This led us to generate the knockout mouse model for Angiotensin Converting Enzyme-2 (ACE2) receptor, one of the molecular factors mediating SARS-CoV-2 entry to the central nervous system, using CRISPR-Cas9 based genome editing tools. ACE2 receptors and Transmembrane Serine Protease-2 (TMPRSS2) are widely expressed in the supporting (sustentacular) cells of human and rodent olfactory epithelium, however, not in the olfactory sensory neurons (OSNs). Hence, acute inflammation induced changes due to viral infection in the olfactory epithelium may explain transient changes in olfactory detectabilities. As ACE2 receptors are expressed in different olfactory centers and higher brain areas, we studied the morphological changes in the olfactory epithelium (OE) and olfactory bulb (OB) of ACE2 KO mice in comparison with wild type animals. Our results showed reduced thickness of OSN layer in the OE, and a decrease in cross-sectional area of glomeruli in the OB. Aberrations in the olfactory circuits were revealed by lowered immunoreactivity toward microtubule associated protein 2 (MAP2) in the glomerular layer of ACE2 KO mice. Further, to understand if these morphological alterations lead to compromised sensory and cognitive abilities, we performed an array of behavioral assays probing their olfactory subsystems’ performances. ACE2 KO mice exhibited slower learning of odor discriminations at the threshold levels and novel odor identification impairments. Further, ACE2 KO mice failed to memorize the pheromonal locations while trained on a multimodal task implying the aberrations of neural circuits involved in higher cognitive functions. Our results thus provide the morphological basis for the sensory and cognitive disabilities caused by the deletion of ACE2 receptors and offer a potential experimental approach to study the neural circuit mechanisms of cognitive impairments observed in long COVID.